Gospodarka mieszkaniowa gminy. Formy współdziałania gminy z podmiotami prywatnymi - Kosiński, Eryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article approaches the problem of housing development under the existing law in Poland. It defines both the material scope of the term “housing” and the personal scope of all units obliged under law to provide the inhabitants with aproper dwelling. Having analyzed the appropriate law, it is possible to state that housing, properly defined, is an obligatory task of acommune in Poland.Moreover, it belongs to the so-called tasks of a“public utility” character. Anyway, it must be underlined there is no universal right to housing either under Polish Constitution or under any act of the Parliament. Acooperation between acommune and aprivate sector in terms of housing development is possible in may ways. On the one hand, there is apossibility to shift the whole development to aprivate sector. It may happen under the contract. On the other hand, there is apossibility a commune undertakes the housing development exclusively, without any participation of aprivate sector. If a commune decides to cooperate with aprivate sector in the housing development area, there are different kinds of public-private partnerships available, and among them there are: BOR Build-Operate-Renew, DBFO Design-Build-Finance-Operate, BOT Build-Operate-Transfer, BOO Build-Own-Operate, or BTL Build-Tranfer-Lease.
Keywords: gmina; gospodarka mieszkaniowa; podmioty prywatne; współdziałanie